Community and contribution: Factors motivating students to participate in an extra-curricular online activity and implications for learning. (12th June 2015) - Reeves, Tony; Gomm, Phil
The human desire to join and participate in communities can be seen as an attempt to satisfy some of our universal human needs. The theory of communities of practice has been widely used to explain how and why humans participate in multiple communities, and a key requirement of a community of practice (CoP) is that members engage in 'joint activities and discussions'. In the current age where social media tools have facilitated the exponential growth of online communities, the term CoP is often used to describe a group of people engaging in online discussion. In the context of online learning, the use of CoP theory can often lead to online discussion being interpreted as a joint activity. This paper argues that the concept of a joint activity as something other than online discussion has been neglected, and that while online discussion may account for the presence of an online community, evidence of joint activities beyond the simple discussion of ideas is required for the community to constitute a true CoP. Using activity theory, the authors investigated the factors motivating students on the Digital Design and Animation course at West Midlands University to participate in a non-formal learning activity involving the co-creation of a digital artefact. The authors believe that a greater understanding of the concept of joint activity, and of the link between co-creating an artefact and members' shared emotional connection, has the potential to refocus our understanding and application of the theory of CoP in the networked era.